2021
DOI: 10.1038/s41467-021-24964-2
|View full text |Cite
|
Sign up to set email alerts
|

Puf6 primes 60S pre-ribosome nuclear export at low temperature

Abstract: Productive ribosomal RNA (rRNA) compaction during ribosome assembly necessitates establishing correct tertiary contacts between distant secondary structure elements. Here, we quantify the response of the yeast proteome to low temperature (LT), a condition where aberrant mis-paired RNA folding intermediates accumulate. We show that, at LT, yeast cells globally boost production of their ribosome assembly machinery. We find that the LT-induced assembly factor, Puf6, binds to the nascent catalytic RNA-rich subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 77 publications
(127 reference statements)
0
20
0
1
Order By: Relevance
“…∆ltv 1 mutants are cold-sensitive, and the genetic interaction between LTV1 and RPS15 is also most pronounced at low temperatures. Cold-sensitive phenotypes are frequently observed upon RNA folding problems [ 54 , 55 ], hence we speculate that an altered rRNA structure occurring in the absence of Ltv1 might be the reason for the genetic interactions with Rps15.…”
Section: Discussionmentioning
confidence: 95%
“…∆ltv 1 mutants are cold-sensitive, and the genetic interaction between LTV1 and RPS15 is also most pronounced at low temperatures. Cold-sensitive phenotypes are frequently observed upon RNA folding problems [ 54 , 55 ], hence we speculate that an altered rRNA structure occurring in the absence of Ltv1 might be the reason for the genetic interactions with Rps15.…”
Section: Discussionmentioning
confidence: 95%
“…Following synthesis of ribosomal subunit precursors in the nucleus, they need to enter the cytoplasm via the nuclear pore prior to combining with RPs to complete the maturation process. Gerhardy and his colleagues reported that the low temperature induced assembly protein, Puf6, primed 60S pre-ribosome nuclear exportation and intervened rRNA compaction, was a momentous temperature-regulated rescuing mechanism underlying countering rRNA misfolding and priming exportation competence 37 . Meanwhile, dedicated chaperones specifically mediate the transportation of RPs to ensure the successful implementation of this process.…”
Section: Ribosome Quality Control Systemmentioning
confidence: 99%
“…[94] rbfA deletion strain exhibits cold-sensitivity and increased levels of an unprocessed precursor of 16S rRNA [94] Notably, in wild-type cells, RbfA is specifically induced at LT [95] suggesting that the 5′ helix of 16S rRNA requires its RNA chaperoning activity to correctly fold at LT. [96] A quantitative proteomic study from our laboratory revealed how the yeast ribosome assembly pathway is rewired to adapt to LT. We found that yeast cells globally induce production of r-proteins and AFs when grown at LT as compared to optimal temperatures. [97] Notably, a significant group of induced proteins were ATP-dependent RNA helicases and components associated with C/D box snoRNAs. [97] An rRNA chaperoning function for snoRNAs has been suggested, [54,98] raising the possibility of whether their induction at LT also facilitates pre-rRNA folding during ribosome assembly under challenging circumstances.…”
Section: Rna Folding At Low Temperaturementioning
confidence: 99%
“…[97] Notably, a significant group of induced proteins were ATP-dependent RNA helicases and components associated with C/D box snoRNAs. [97] An rRNA chaperoning function for snoRNAs has been suggested, [54,98] raising the possibility of whether their induction at LT also facilitates pre-rRNA folding during ribosome assembly under challenging circumstances.…”
Section: Rna Folding At Low Temperaturementioning
confidence: 99%
See 1 more Smart Citation